THE INFLUENCE OF INVESTIGATION GROUP TYPE COOPERATIVE LEARNING ON THE CRITICAL THINKING ABILITY OF STUDENTS OF THE ISLAMIC RELIGIOUS EDUCATION PROGRAM UNIVERSITY OF SINGAPERBANGSA KARAWANG - Makbul, M.; Ferianto, Ferianto; Husain, Nurjannah; Farida, Nur Aini; Munafiah, Nida'ul (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to determine the effect of group investigation learning (X) on the critical thinking abilities (Y) of PAI undergraduate students at Singaperbangsa University Karawang. The research method used a quantitative approach with a relational study type, and the research population was 1140 students with a purposive sampling technique. The research sample was set at 110 students; the instruments used were questionnaires and project-based performance test results. Group Investigation Cooperative Learning, 16% in the low category, 69% in the medium category, and 15% in the high category. So, the cooperative learning group, the Investigation of Islamic Religious Education students, is in the medium category. Students' critical thinking ability is 7% in the low category, 79% in the medium category, and 14% in the high category. So, learning essential thinking skills for Islamic Religious Education students is in the medium category. The R Square value = 0.756; thus, it can be concluded that there is an influence of group investigation learning (X) on critical thinking abilities (Y) of PAI S-1 students at Singaperbangsa University Karawang of 75.6%. In comparison, 24.4% is influenced by other variables that are not variables in this research.